I believe you need to solve this using the quadratic formula!
To begin, this is what it is:
x= -b ± √ b^2 - 4ac / 2a
Just plug in what you have in your problem...
2 being a, 13 being b, and -24 being c.
So we get:
x= -13 ± √13^2 - 4(2)(-24) / 2(2)
x= -13 ± √169 - 8 (-24) / 4
x= -13 ± √169 + 192 / 4
x= -13 ± √361 / 4
The square root of 361 is 19.
So you have: -13 ± 19 / 4.
Here's where you take the equation -13 ± 19 and put the addition and subtraction sign to use.
-13 - 19 = -32
and
-13 + 19 = 6
Now all is left to do is divide the two numbers by 4.
-32/4 = -8
and
6/4 = 3/2
x = -8, 3/2